Multidomain Optimised Hidden Web Crawler (International Journal of Engineering and Computer Science, 2018)
Although  hidden web crawlers seems to be in great use while searching for hidden data, but the curent hidden web crawlers works on only one domain which proves to be a major drawback in the compatibilty of the searching process. This paper highlights the extended working of the hidden crawlers by providing multiple domain feature which not only helps the user to get high quality content but also makes searching process faster and more broader. The multiple domain system can work on two or more than two domains depending upon the requirement. The multiple domain system also provides a fast linkage between various webpages using multiple links. Thus the project proves to be an useful extension of this extensive tool.